Molded underfill composition for TSV
Patent Information
- Application Number
- KR1020220057882
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-27
- Filing Date
- 2022-05-11
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2042-05-11
Smart Images

Figure 112022050070099-PAT00006_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a liquid epoxy resin composition suitable for use as a mold underfill composition for TSVs. Background Technology
[0002] Recently, in order to further improve the performance of electronic devices, it is required to increase the density of wiring on chips within electronic components constituting electronic devices. However, increasing the wiring density per unit area of a chip through further miniaturization of wiring layers is approaching a limit. Therefore, it has become common practice to further increase the wiring density per unit area of a chip by stacking multiple chips three-dimensionally (see, for example, Patent Document 2).
[0003] In such techniques, connections between stacked chips are required. Through Silicon Via (TSV) technology is increasingly being adopted for such connections. TSV technology is a technique in which an electrode is installed that penetrates a silicon semiconductor chip in the thickness direction, and connections between stacked chips are made using this electrode.
[0004] In the manufacture of electronic components comprising such stacked multiple chips, a conventional process was used in which, after sealing between the wafer and the chip or between the chips each time a chip is stacked, the entire stacked chip is covered with a liquid curable resin composition and each chip is subjected to compression molding to form the external shape of the electronic component (overmolding). However, in recent years, in order to improve manufacturing efficiency, a technique is increasingly being used in which all chips are stacked without sealing, and then the entire stacked chip is covered with a liquid curable resin composition and each chip is subjected to compression molding to perform sealing between the wafer and the chip and between each chip, as well as forming the external shape of the electronic component, in a single process. The curable resin composition used in this technique is called a mold underfill composition for TSV or a mold underfill material for TSV (see, for example, Patent Document 1). As a mold underfill composition for TSV, a liquid epoxy resin composition is mainly used.
[0005] Such mold underfill compositions sometimes contain fillers and / or colorants. The former is mainly added for purposes such as reducing the coefficient of thermal expansion and improving strength in the cured product imparted by the mold underfill composition. The latter is added to reduce the influence of light on the wiring within electronic components, but the former is added in combination with the latter to assist the function of the latter (see, for example, Patent Documents 4 and 5). Prior art literature
[0006] Patent Document 1: Specification of International Patent Publication No. WO2019 / 146617 Patent Document 2: Japanese Patent Publication No. 2010-074120 Patent Document 3: Japanese Patent Publication No. Hei 2-88629 Patent Document 4: Japanese Patent Publication No. 2020-015873 Patent Document 5: Japanese Patent No. 5579764 The problem to be solved
[0007] However, it was found that electronic components manufactured using a conventional liquid epoxy resin composition as a mold underfill composition for TSVs and such a technique have low reliability.
[0008] Various reliability tests for electronic components are known, but one of them is the High-Speed Accelerated Life Test (HAST test), which is a reliability test conducted under high temperature and high humidity conditions (e.g., 130°C, relative humidity 85%) where corrosion inside the electronic component (especially the metal part) is accelerated. The HAST test includes tests conducted under conditions where no bias voltage is applied to the electronic component being tested (HAST test without bias) and tests conducted under conditions where a bias voltage is applied (HAST test with bias). It has been found that when electronic components manufactured by a technique in which a conventional liquid epoxy resin composition is used as a mold underfill composition for TSVs, and the sealing between the wafer and the chip and between each chip, as well as the molding of the external shape of the electronic component, are subjected to reliability testing, particularly a bias HAST test, they are prone to short circuits in a short period of time. This problem was previously unknown and was discovered for the first time by the inventors of the present invention.
[0009] The present invention aims to provide a liquid epoxy resin composition suitable for use as a mold underfill composition for TSVs, which, in order to solve the problems of the aforementioned prior art, provides a cured product that exhibits good injectability and does not cause a short circuit in a bias HAST test, enables the efficient manufacturing of electronic components including high-density wiring formed by techniques such as TSVs, and also provides sufficient reliability to such electronic components. means of solving the problem
[0010] The inventors have arrived at the present invention as a result of repeated research to solve the above-mentioned problem.
[0011] That is, the present invention is not limited to but includes the following inventions.
[0012] 1. As a mold underfill composition for TSV, the following (A) to (D):
[0013] (A) Epoxy resin;
[0014] (B) Curing agent;
[0015] (C) Filler; and
[0016] (D) Carbon Black
[0017] Includes,
[0018]
[0019] [In the expression, n is an integer from 1 to 15.]
[0020] It includes an aliphatic epoxy resin appearing as, and
[0021] The above (C) filler comprises a filler with an average particle size of 0.1㎛ to 1.0㎛, and
[0022] When the mass of the above (A) epoxy resin is 100 parts by mass, the content of the above (D) carbon black is 0.1 parts by mass or more and 1.5 parts by mass or less, and also
[0023] chloride ions (C1 - A TSV mold underfill composition having a content of ) of 0.1 ppm or more and less than 11.0 ppm with respect to the total mass of the above TSV mold underfill composition.
[0024] 2. (C) A mold underfill composition for TSVs described in the preceding claim 1, wherein, when the total mass of the filler is 100 parts by mass, the content of particles having a particle size greater than 1 μm in the (C) filler is less than 1.0 part by mass.
[0025] 3. A mold underfill composition for TSV described in claim 1 or 2, wherein, when the total mass of the mold underfill composition for TSV is 100 parts by mass, (C) the filler content is 65 to 90 parts by mass.
[0026] 4. (A) A mold underfill composition for TSVs described in any one of claims 1 to 3, further comprising an epoxy resin having an aromatic ring in its molecule.
[0027] 5. (B) A mold underfill composition for TSVs described in any one of claims 1 to 4, comprising at least one curing agent selected from the group consisting of phenol compounds, acid anhydrides, non-cyclic amine compounds and nitrogen-containing heterocyclic compounds.
[0028] 6. (E) A mold underfill composition for TSVs described in any one of claims 1 to 5, further comprising a silicon-based additive.
[0029] 7. (F) A mold underfill composition for TSVs described in any one of claims 1 to 6, further comprising a coupling agent.
[0030] 8. (G) A mold underfill composition for TSVs described in any one of claims 1 to 7, further comprising a migration inhibitor.
[0031] 9. A mold underfill composition for TSV described in any one of claims 1 to 8, wherein, when the total mass of the mold underfill composition for TSV is 100 parts by mass, the content of particles with a diameter greater than 1 μm is less than 1.0 part by mass.
[0032] 10. A semiconductor package having a semiconductor device sealed by a mold underfill composition for a TSV as described in any one of claims 1 to 9. Effects of the invention
[0033] The mold underfill composition for TSVs of the present invention exhibits good injectability and appropriate sealing properties. In addition, electronic components containing a cured product obtained by curing the mold underfill composition for TSVs of the present invention do not cause a short circuit over a long period of time during a bias HAST test. Therefore, by using the mold underfill composition for TSVs of the present invention, sufficient reliability can be imparted to electronic components containing high-density wiring formed by techniques such as TSVs. Brief explanation of the drawing
[0034] Figure 1 is a diagram illustrating the sequence of sealing and overmolding by a mold underfill composition for TSV. FIG. 2 is a schematic diagram illustrating the positions of a silicon wafer, a silicon chip, and a spacer used to evaluate the injectability of a mold underfill composition for TSV. (A) is a schematic diagram showing the position of a silicon chip placed on a silicon wafer. (B) is a schematic diagram illustrating the positions of a silicon chip and a spacer on a silicon wafer. Figure 3 is a micrograph showing the evaluation results of the injectability of a mold underfill composition for TSV. (A) is a micrograph of the polished surface of a test specimen prepared using a mold underfill composition for TSV with insufficient injectability. (B) is a micrograph of the polished surface of a test specimen prepared using a mold underfill composition for TSV with good injectability. Figure 4 is a schematic diagram illustrating the shape of a comb-shaped electrode used in a bias HAST test. Specific details for implementing the invention
[0035] Hereinafter, embodiments of the present invention will be described in detail.
[0036] The present invention is as follows (A) to (D):
[0037] (A) Epoxy resin;
[0038] (B) Curing agent;
[0039] (C) Filler; and
[0040] (D) Carbon Black
[0041] The present invention relates to a mold underfill composition for TSV comprising. In this composition,
[0042]
[0043] [In the expression, n is an integer from 1 to 15.]
[0044] It includes an aliphatic epoxy resin represented as. The filler (C) comprises a filler with an average particle size of 0.1 μm to 1.0 μm. When the mass of the epoxy resin (A) is 100 parts by mass, the content of the carbon black (D) is 0.1 parts by mass or more and 1.5 parts by mass or less. In addition, chloride ions (C1 ― The content of ) is 0.1 ppm or more and less than 11.0 ppm with respect to the total mass of the mold underfill composition for TSV. The above components (A) to (D) included in the mold underfill composition for TSV of the present invention will be described below.
[0045] (A) Epoxy resin
[0046] The mold underfill composition for TSV according to the present invention contains an epoxy resin. It is preferable to use an epoxy resin that is liquid at room temperature. In addition, it is preferable to use a liquid epoxy resin with a viscosity within the range of 10 to 5000 mPa·s. By using a liquid epoxy resin, a mold underfill composition for TSV with low viscosity and excellent fluidity can be obtained.
[0047] In addition, in the mold underfill composition for TSV according to the present invention, the content of the epoxy resin is preferably 10 to 35 parts by mass when the total mass of the mold underfill composition for TSV is 100 parts by mass, more preferably 12 to 32 parts by mass, and particularly preferably 15 to 30 parts by mass. By maintaining this range, the increase in viscosity of the mold underfill composition for TSV can be suppressed, and the coefficient of thermal expansion of the cured product of the mold underfill composition for TSV can also be reduced.
[0048]
[0049] [In the expression, n is an integer from 1 to 15.]
[0050] It includes an aliphatic epoxy resin (diglycidyl ether of (poly)tetramethylene glycol) as shown. n in this aliphatic epoxy resin can be calculated from the molecular weight of the epoxy resin (number average molecular weight equivalent to standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as the elution solvent). By including this aliphatic epoxy resin, the occurrence of warping after curing of the mold underfill composition for TSV applied to a wafer on which a semiconductor chip is mounted can be suppressed.
[0051] As an aliphatic epoxy resin represented by the above formula (I), commercially available products such as “YX7400” (manufactured by Mitsubishi Chemical Corporation) and “Epogosei PT (General Grade)” (manufactured by Yokkaichi Synthetic Co., Ltd.) may be used.
[0052] In the mold underfill composition for TSV according to the present invention, the epoxy resin may include other epoxy resins in addition to the aliphatic epoxy resin represented by Formula (I). As other epoxy resins, epoxy resins used as sealing materials may be used. It is preferable that this epoxy resin be a polyfunctional epoxy resin with two or more functional groups. Examples of polyfunctional epoxy resins include:
[0053] Monocyclic aromatic epoxy resins such as catechol diglycidyl ether, resorcin diglycidyl ether, phthalate diglycidyl ester, 2,5-diisopropylhydroquinone diglycidyl ether, hydroquinone diglycidyl ether, etc.;
[0054] Alicyclic epoxy resins such as 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexylcarboxylate, bis(3,4-epoxycyclohexyl)adipate, vinylcyclohexene monoepoxide, diepoxylimonene, etc.;
[0055] Bisphenol-type epoxy resins such as bisphenol A, bisphenol F, bisphenol AD, and bisphenol S;
[0056] A mixture of oligomers obtained by partial polymerization of bisphenol-type epoxy resin;
[0057] Ring-hydrogenated bisphenol-type epoxy resin;
[0058] Tetramethylbis(4-hydroxyphenyl)methanediglycidyl ether; Tetramethylbis(4-hydroxyphenyl)etherdiglycidyl ether;
[0059] Biphenyl-type or tetramethylbiphenyl-type epoxy resins and resins in which the rings thereof are hydrogenated;
[0060] Fluorene-type epoxy resins such as bisphenolfluorene-type epoxy resin and biscresolfluorene-type epoxy resin;
[0061] Examples include naphthalene-type epoxy resins.
[0062] In addition, as a polyfunctional epoxy resin, for example,
[0063] Polyfunctional glycidylamine type epoxy resins such as aminophenol type epoxy resins including triglycidyl-ρ-aminophenol, aniline type epoxy resins such as diglycidylaniline, toluidine type epoxy resins such as diglycidylorthotoluidine, and diaminodiphenylmethane type epoxy resins such as tetraglycidyldiaminodiphenylmethane;
[0064] Dicyclopentadiene-type epoxy resin;
[0065] Examples of polyfunctional glycidyl ethers include trimethylolalkane-type epoxy resins such as trimethylolpropane triglycidyl ether, trimethylolmethane triglycidyl ether, and trimethylolethane triglycidyl ether.
[0066] In addition, other epoxy resins, such as aliphatic epoxy resins, silylated epoxy resins, heterocyclic epoxy resins, diallylbisphenol A type epoxy resins, polyarylene ether diglycidyl ethers, etc., may also be used in combination.
[0067] In the mold underfill composition for TSV of the present invention, the epoxy resins may be used alone or two or more may be used in combination.
[0068] The above other epoxy resin is preferably an epoxy resin having an aromatic ring in its molecule. In one embodiment of the present invention, the epoxy resin further comprises an epoxy resin having an aromatic ring in its molecule in addition to the aliphatic epoxy resin represented by formula (I). By using an epoxy resin having an aromatic ring in its molecule, the curability of the mold underfill composition for TSV is improved, and the heat resistance is improved, resulting in a favorable bias HAST test result.
[0069] In addition, the mass ratio of the aliphatic epoxy resin represented by the above formula (I) and the epoxy resin having an aromatic ring is preferably 5:95 to 50:50, more preferably 10:90 to 45:55, and particularly preferably 20:80 to 40:60. By setting the above mass ratio to the range, the occurrence of warping after curing of the mold underfill composition for TSV applied to a wafer on which a semiconductor chip is mounted can be suppressed, and good bias HAST test results can also be obtained.
[0070] As an epoxy compound having an aromatic ring in the molecule, known or commonly used aromatic epoxy compounds may be used and are not particularly limited.
[0071] Specific examples of epoxy compounds having an aromatic ring in the molecule include:
[0072] Glycidyl ethers of phenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, catechol, resorcinol, etc.
[0073] Glycidyl ether ester of a hydroxycarboxylic acid such as ρ-hydroxybenzoic acid;
[0074] Monoglycidyl esters or polyglycidyl esters of carboxylic acids such as benzoic acid, phthalic acid, terephthalic acid, etc.;
[0075] Glycidylamine-type epoxy compounds such as diglycidylaniline, diglycidyltoluidine, triglycidyl-ρ-aminophenol, tetraglycidyl-m-xylenediamine;
[0076] Examples include epoxy compounds having a naphthalene backbone, such as glycidyl esters of naphthol and glycidyl ether esters of β-hydroxynaphthoic acid. Additionally, novolak compounds obtained by novolakizing phenols such as phenol, catechol, and resorcinol may be used. Among these, glycidylamine-type epoxy compounds are preferred.
[0077] (B) Curing agent
[0078] The mold underfill composition for TSVs of the present invention contains a curing agent. This curing agent is not particularly limited as long as it can cure the epoxy resin of (A). Examples of curing agents that can be used in the mold underfill composition for TSVs of the present invention include phenol compounds, acid anhydrides, amine compounds (particularly, non-cyclic amine compounds), nitrogen-containing heterocyclic compounds (particularly, imidazole compounds), phosphorus compounds, and organometallic compounds. In some embodiments, among these, basic ones are used.
[0079] Examples of the above-mentioned phenolic compounds include phenolic resins, particularly novolak resins obtained by condensing formaldehyde with phenols or naphthols (e.g., phenol, cresol, naphthol, alkylphenol, bisphenol, terpenephenol, etc.). Examples of novolak resins include phenol novolak resin, ο-cresol novolak resin, ρ-cresol novolak resin, α-naphthol novolak resin, β-naphthol novolak resin, t-butylphenol novolak resin, bisphenol A type novolak resin, xylene-modified novolak resin, decalin-modified novolak resin, etc. Examples of other phenolic resins include dicyclopentadiene cresol resin, polyparavinylphenol, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, and poly(di-ρ-hydroxyphenyl)methane.
[0080] Examples of the above acid anhydrides include phthalic anhydride; alkylhexahydrophthalic anhydride such as hexahydrophthalic anhydride; methylhexahydrophthalic anhydride; tetrahydrophthalic anhydride; alkyltetrahydrophthalic anhydride such as trialkyltetrahydrophthalic anhydride and 3-methyltetrahydrophthalic anhydride; hymic anhydride; citric acid; trimellitic anhydride; pyrromellitic anhydride, etc. Among these, methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride are preferred.
[0081] Examples of the above (non-cyclic)amine compounds include 2,4,6-tris(dimethylaminomethyl)phenol, diethylamine, triethylamine, diethylenetetramine, triethylenetetramine, tetramethyldiaminodiphenylmethane, tetraethyldiaminodiphenylmethane, diethyldimethyldiaminodiphenylmethane, dimethyldiaminotoluene, diaminodibutyltoluene, diaminodipropyltoluene, diaminodiphenylsulfone, diaminoditolylsulfone, diethyldiaminotoluene, bis(4-amino-3-ethylphenyl)methane, polytetramethyleneoxide-di-ρ-aminobenzoate, and 4,4-dimethylaminopyridine. The amine compounds may also be amine adducts.
[0082] Examples of nitrogen-containing heterocyclic compounds include imidazoles such as 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, diazabicycloundecene (DBU), DBU-phenol salt, DBU-octylate, DVU-ρ-toluenesulfonate, DBU-formate, DBU-orthophthalate, Examples include DBU-phenol novolak resin salts, DVU-based tetraphenyl borate salts, diazabicyclononene (DBN), DBN-phenol novolak resin salts, diazabicyclooctane, pyrazol, oxazole, thiazole, imidazoline, pyrazine, morpholine, thiazine, indole, isoindole, benzimidazole, purine, quinoline, isoquinoline, quinoxaline, cinnoline, pteridine, etc. Nitrogen-containing heterocyclic compounds may be used that form adducts with epoxy resins or isocyanate compounds, or are microencapsulated.
[0083] Examples of the above phosphorus compounds include trialkylphosphine compounds such as tributylphosphine and triarylphosphine compounds such as triphenylphosphine.
[0084] Examples of the above organometallic compounds include zinc naphthenate, cobalt naphthenate, tin octylate, cobalt octylate, bis-acetylacetonatocobalt (II) and tris-acetylacetonatocobalt (III).
[0085] In the present invention, it is preferable that the curing agent comprises at least one selected from the group consisting of phenol compounds, acid anhydrides, non-cyclic amine compounds, and nitrogen-containing heterocyclic compounds, and it is more preferable that it comprises nitrogen-containing heterocyclic compounds. The nitrogen-containing heterocyclic compound may be latent, and a microcapsule-type latent curing agent may be used.
[0086] It is particularly preferable that the nitrogen-containing heterocyclic compound is an imidazole compound. Examples of imidazole compounds include 2-substituted imidazole compounds such as imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl2-methylimidazole, 2-ethyl4-methylimidazole, 2-phenylimidazole, 2-phenyl4-methylimidazole, 1-benzyl2-methylimidazole, 1-benzyl2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl2-methylimidazole, 1-cyanoethyl2-ethyl4-methylimidazole, 1-cyanoethyl2-undecylimidazole, and 1-cyanoethyl2-phenylimidazole; Trimellitates such as 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, etc.; triazine compounds such as 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, etc.; Examples include isocyanurate adducts of 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, isocyanurate adducts of 2-phenylimidazole, isocyanurate adducts of 2-methylimidazole, isocyanurate adducts of 2-phenyl-4,5-dihydroxymethylimidazole, and isocyanurate adducts of 2-phenyl-4-methyl-5-dihydroxymethylimidazole.
[0087] As the above-mentioned microcapsule-type curing agent, for example, a dispersion in which powder of an amine compound (including nitrogen-containing heterocyclic compounds) is dispersed in a liquid epoxy resin may be used. This amine compound may be selected from, for example, aliphatic primary amines, alicyclic primary amines, aromatic primary amines, aliphatic secondary amines, alicyclic secondary amines, aromatic secondary amines, imidazole compounds, and imidazoline compounds. This amine compound may also be used in the form of a reaction product with a carboxylic acid, sulfonic acid, isocyanate, epoxide, etc. These compounds may be used alone or in combination of two or more types. For example, the above-mentioned amine compound may be used in combination with the reaction product with the carboxylic acid, sulfonic acid, isocyanate, or epoxide. The volume average particle size of the powder of the above-mentioned amine compound is preferably 50 μm or less, and more preferably 10 μm or less. In addition, it is preferable that the powder of the above amine compound has a melting point or softening point of 60°C or higher in order to suppress thickening at 25°C.
[0088] In the mold underfill composition for TSV according to the present invention, the curing agent may be used alone or two or more may be used in combination. In the present invention, the curing agent is preferably an imidazole compound, and it is more preferable to use an imidazole compound and a phenol compound in combination. By using an imidazole compound and a phenol compound in combination, the curability can be increased while improving storage stability.
[0089] In the mold underfill composition for TSV according to the present invention, the content of the curing agent is preferably 1 to 20 mass% with respect to (A) epoxy resin, more preferably 2 to 15 mass%, and particularly preferably 3 to 10 mass%. By setting the content within this range, the curing time of the mold underfill composition for TSV is not excessively long, thereby improving the productivity of electronic components including high-density wiring formed by techniques such as TSV, suppressing the occurrence of warping after curing of the mold underfill composition for TSV applied to a wafer on which a semiconductor chip is mounted, and also improving the storage stability of the mold underfill composition for TSV.
[0090] (C) Filler
[0091] The mold underfill composition for TSV of the present invention contains a filler.
[0092] Examples of fillers used in the present invention include, but are not limited to, fillers composed of silica (fused silica, crystalline silica, etc.), alumina, talc, calcium carbonate, titanium white, Bengala, silicon carbide, boron nitride (BN), glass beads, etc. However, in the present invention, carbon black is not a filler. In the mold underfill composition for TSV of the present invention, the filler may be used alone or two or more types may be used in combination.
[0093] In addition, the filler may be surface-treated with a surface treatment agent, for example, a silane coupling agent (which may have substituents such as phenyl groups, vinyl groups, methacryloyl groups, etc.). By using a surface-treated filler, the viscosity of the mold underfill composition for TSV is reduced, thereby improving injectability.
[0094] In terms of reducing the thermal expansion coefficient of the cured product imparted by the mold underfill composition for TSV of the present invention, it is preferable to use silica powder as a filler, and it is more preferable to use fused silica powder. Examples of fused silica powder include spherical fused silica powder and crushed fused silica powder, but in terms of the fluidity of the mold underfill composition for TSV, it is more preferable to use spherical fused silica powder (especially one composed of particles with a high degree of sphericity) as a filler.
[0095] The filler used in the present invention comprises a filler with an average particle size of 0.1 μm to 1.0 μm, preferably 0.1 μm to 0.6 μm, and more preferably 0.1 μm to 0.3 μm. If the filler does not include a filler with an average particle size of 0.1 μm to 1.0 μm, the mold underfill composition exhibits inappropriate viscosity and / or injectability. In addition, the viscosity of the mold underfill composition at 25°C, measured using a rotational viscometer at a rotational speed of 20 rpm, is preferably 20 to 400 Pa·s, more preferably 40 to 300 Pa·s, and particularly preferably 60 to 200 Pa·s. By having the viscosity within this range, the injectability of the mold underfill composition for TSV is improved, and the leakage of the mold underfill composition for TSV from the mold during compression molding can be suppressed. In addition, “injectability” in this invention refers to the degree of ease of filling the mold underfill composition for TSV between the silicon chip and the silicon wafer during compression molding.
[0096] The average particle size of the filler is the particle size at 50% of the cumulative volume of the volumetric particle size distribution (D 50 It is obtained as ). More specifically, using a sample randomly extracted from a population, the particle size distribution can be measured by a laser diffraction scattering particle size distribution measuring device, and the average particle size, etc. can be obtained based on this particle size distribution.
[0097] In the present invention, from the perspective of injectability, it is particularly preferable that the content of particles with a particle size larger than 1 μm in the filler is less than 1.0 part by mass when the total mass of the filler is 100 parts by mass. In addition, the mold underfill composition for TSV of the present invention may further include, as an optional component, a filler with an average particle size of less than 0.1 μm, within a range that does not adversely affect the characteristics of the composition.
[0098] In the mold underfill composition for TSV according to the present invention, the filler content is preferably 65 to 90 parts by mass when the total mass of the mold underfill composition for TSV is 100 parts by mass, more preferably 68 to 88 parts by mass, and particularly preferably 70 to 85 parts by mass.
[0099] (D) Carbon Black
[0100] The mold underfill composition for TSV according to the present invention contains carbon black. Considering the possibility that wiring within electronic components may be affected by light, the use of carbon black is important. The carbon black is not particularly limited, and any carbon black commonly used as a carbon black included in epoxy resin compositions can be appropriately selected and adopted. Examples of such carbon black include acetylene black, furnace black, Ketjen black, channel black, lamp black, thermal black, etc. These may be used individually or in combination of two or more types.
[0101] In the present invention, carbon black may be used in combination with other black pigments. Other black pigments may include black organic pigments, mixed organic pigments, black inorganic pigments, etc. Examples of black organic pigments include perylene black and aniline black. Examples of mixed organic pigments include a pseudo-black pigment produced by mixing at least two types of pigments selected from red, blue, green, purple, yellow, magenta, cyan, etc. Examples of black inorganic pigments include fine particles of graphite, metals and their oxides (including complex oxides), sulfides, nitrides, etc. Examples of these metals include titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, silver, etc.
[0102] In addition, carbon black may be used in combination with other coloring agents such as dyes.
[0103] In the mold underfill composition for TSV according to the present invention, the carbon black content is 0.1 parts by mass or more and 1.5 parts by mass or less when the mass of the (A) epoxy resin is 100 parts by mass. The carbon black content is preferably 0.1 parts by mass or more and 1.3 parts by mass or less, and more preferably 0.1 parts by mass or more and 1.1 parts by mass or less. Furthermore, when the total mass of the mold underfill composition for TSV is 100 parts by mass, the carbon black content is preferably 0.01 parts by mass or more and 0.60 parts by mass or less, more preferably 0.01 parts by mass or more and 0.45 parts by mass or less, and even more preferably 0.01 parts by mass or more and 0.30 parts by mass or less.
[0104] If the carbon black content falls below the above range, light shielding becomes insufficient, and there is a risk that the wiring within the electronic component may be affected by light. If the carbon black content exceeds the above range, the electronic component obtained by packaging multiple chips stacked using TSV technology using the TSV mold underfill composition is prone to short circuits during the bias HAST test. In other words, the reliability of such electronic components is reduced. It was first discovered by the inventors that the carbon black content in the TSV mold underfill composition affects the reliability of electronic components manufactured using TSV technology.
[0105] In addition, in the mold underfill composition for TSV of the present invention, chloride ions (Cl - The content of ) is 0.1 ppm or more and less than 11.0 ppm with respect to the total mass of the mold underfill composition for TSV. This content is preferably 0.1 ppm or more and less than 10.8 ppm, more preferably 0.1 ppm or more and less than 10.0 ppm, and even more preferably 0.1 ppm or more and less than 7.0 ppm. If the chloride ion content is 11.0 ppm or more, electronic components obtained by packaging multiple chips stacked using TSV technology with the mold underfill composition for TSV are prone to short circuits during a bias HAST test. In other words, the reliability of such electronic components is reduced. On the other hand, from the perspective of commercial availability, it is preferable that the chloride ion content be 0.1 ppm or more.
[0106] As previously described, in the manufacture of electronic components comprising multiple stacked chips, a conventional process has been used in which sealing is performed between the wafer and the chip, or between the chips themselves, after each chip is stacked, followed by overmolding. In such a process, a resin composition having a lower chloride ion content compared to the resin composition used for overmolding was used for sealing.
[0107] In this regard, when sealing and overmolding are performed as a single process using a mold underfill composition for TSVs, the same resin composition must be used for both. Conventional resin compositions for sealing are unsuitable as mold underfill compositions for TSVs due to reasons such as moisture resistance and ion leaching resistance. On the other hand, when an electronic component containing multiple stacked chips is manufactured using a conventional resin composition for overmolding as a mold underfill composition for TSVs, the resulting electronic component is prone to short circuits during bias HAST testing. In other words, such an electronic component exhibits low reliability.
[0108] Under these circumstances, the inventors, through various investigations, discovered that when the chloride ion content in addition to the carbon black content in the mold underfill composition for TSV is within the above range, an electronic component containing a cured product obtained by curing the mold underfill composition for TSV does not cause a short circuit over a long period of time in a bias HAST test, and that such low reliability is due to the excessively high chloride ion content in conventional mold underfill compositions for TSV. This was discovered for the first time by the inventors.
[0109] The chloride ion content can be measured by extracting the sample with pure water under high heat and high pressure (e.g., 121°C and 2 atmospheres for 20 hours) and analyzing the obtained extract by ion chromatography. However, if it is difficult to measure the chloride ion content for the mold underfill composition for TSV according to the present invention, this content is considered to be equivalent to the chloride ion content measured by the above method for the cured product obtained by curing the mold underfill composition for TSV.
[0110] The mold underfill composition for TSV of the present invention may, if desired, contain optional components, for example, those described below, in addition to the essential components (A) to (D).
[0111] (E) Silicon-based additives
[0112] The mold underfill composition for TSVs of the present invention may include a silicon-based additive if desired. In one embodiment, the mold underfill composition for TSVs of the present invention further includes a silicon-based additive. Including a silicon-based additive is desirable from the perspective of improving the fluidity of the mold underfill composition for TSVs. The silicon-based additive is preferably a dialkylpolysiloxane (as the alkyl group bonded to Si, examples include methyl, ethyl, etc.), particularly a dimethylpolysiloxane. In addition, the silicon-based additive may be a modified dialkylpolysiloxane, for example, an epoxy-modified dimethylpolysiloxane. Specific examples of silicon-based additives include KF69 (dimethylsilicon oil, manufactured by Shin-Etsu Silicon) and SF8421 (epoxy-modified silicone oil, manufactured by Toray Dow Silicon). The silicon-based additive may be used alone or in combination of two or more types.
[0113] When the mold underfill composition for TSV of the present invention includes a silicon-based additive, the amount of the silicon-based additive is preferably 0.1 to 1.0 parts by mass per 100 parts by mass of (A) epoxy resin, and more preferably 0.25 to 1 part by mass.
[0114] (F) Coupling agent
[0115] The mold underfill composition for TSVs of the present invention may include a coupling agent if desired. In one embodiment, the mold underfill composition for TSVs of the present invention further includes a coupling agent. It is desirable to include a coupling agent, particularly a silane coupling agent, from the viewpoint of improving adhesive strength. As a coupling agent, various silane coupling agents such as epoxy-based, amino-based, vinyl-based, methacrylic-based, acrylic-based, and mercapto-based may be used. Specific examples of silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, vinyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, ρ-styryltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 3-ureidpropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more types.
[0116] When the mold underfill composition for TSV of the present invention includes a coupling agent, the amount of the coupling agent is preferably 0.01 to 5 parts by mass per 100 parts by mass of (A) epoxy resin, and more preferably 0.1 to 3 parts by mass.
[0117] (G) Migration inhibitor
[0118] The mold underfill composition for TSVs of the present invention may, if desired, include a migration inhibitor. In one embodiment, the mold underfill composition for TSVs of the present invention further includes a migration inhibitor. Migration is a phenomenon in which metal in a wiring pattern is leached out by an electrochemical reaction, causing a decrease in resistance value. The inclusion of a migration inhibitor is desirable from the perspective of improving reliability in electronic components. Specific examples of migration inhibitors include xanthines such as caffeine, theophylline, theobromine, and paraxanthine; and tocols such as 5,7,8-trimethyltocol (α-tocopherol), 5,8-dimethyltocol (β-tocopherol), 7,8-dimethyltocol (γ-tocopherol), and 8-methyltocol (δ-tocopherol). Examples include tocotrienos such as 5, 7, 8-trimethyltocotrienol (α-tocotrienol), 5, 8-dimethyltocotrienol (β-tocotrienol), 7, 8-dimethyltocotrienol (γ-tocotrienol), and 8-methyltocotrienol (δ-tocotrienol); benzotriazoles such as benzotriazole, 1H-benzotriazole-1-methanol, and alkylbenzotriazoles; triazines such as 2, 4-diamino-6-vinyl-S-triazine, 2, 4-diamino-6-[2'-ethyl-4-methylimidazole-(1)]-ethyl-S-triazine, and 2, 4-diamino-6-methacryloyloxyethyl-S-triazine; and isocyanuric acid adducts of the above benzotriazoles or triazines. These migration inhibitors may be used alone or in combination of two or more.
[0119] When the mold underfill composition for TSV of the present invention includes a migration inhibitor, the amount of the migration inhibitor is preferably 0.01 to 5 parts by mass per 100 parts by mass of (A) epoxy resin, and more preferably 0.1 to 3 parts by mass.
[0120] (H) Stabilizer
[0121] The mold underfill composition for TSVs of the present invention may include a stabilizer if desired. The stabilizer may be included in the mold underfill composition for TSVs of the present invention to improve storage stability and extend the working time. Various known stabilizers may be used as stabilizers for one-component adhesives based on epoxy resin, but at least one selected from the group consisting of liquid boric acid ester compounds, aluminum chelates, and organic acids is preferred due to the excellent effect of improving storage stability.
[0122] Examples of liquid boric acid ester compounds include 2,2'-oxybis(5,5'-dimethyl-1,3,2-oxaborinan), trimethylborate, triethylborate, tri-n-propylborate, triisopropylborate, tri-n-butylborate, tripentylborate, trialylborate, trihexylborate, tricyclohexylborate, trioctylborate, trinonylborate, tridecylborate, tridodecylborate, trihexadecylborate, trioctadecylborate, tris(2-ethylhexyloxy)borane, bis(1,4,7,10-tetraoxaundecyl)(1,4,7,10,13-pentaoxatetradecyl)(1,4,7-trioxaundecyl)borane, tribenzylborate, triphenylborate, Examples include tri-o-tolylborate, tri-m-tolylborate, and triethanolamine borate. Liquid boric acid ester compounds are preferred because they are liquid at room temperature (25°C), which allows for keeping the viscosity of the mold underfill composition for TSV low. As an aluminum chelate, for example, aluminum chelate A can be used. As an organic acid, for example, barbituric acid can be used.
[0123] When a stabilizer is included, the amount of stabilizer is preferably 0.01 to 30 parts by mass per 100 parts by mass of (A) epoxy resin, more preferably 0.05 to 25 parts by mass, and even more preferably 0.1 to 20 parts by mass.
[0124] (I) Other additives
[0125] The mold underfill composition for TSV according to the present invention may, if desired, include other additives, such as ion trapping agents, leveling agents, antioxidants, defoaming agents, thixotropic agents, viscosity modifiers, flame retardants, solvents, etc., to the extent that the intent of the present invention is not compromised. The type and amount of each additive are in accordance with commercial law.
[0126] In addition, in the mold underfill composition for TSV of the present invention, one or more of the components included therein (including components (A) to (D)) may exist as fine particulate solids. In the present invention, from the perspective of injectability, it is preferable that the content of particles with a particle size larger than 1 μm is less than 1.0 part by mass when the total mass of the mold underfill composition for TSV is 100 parts by mass.
[0127] The method for preparing the mold underfill composition for TSVs according to the present invention is not particularly limited. For example, components (A) to (D) and, if desired, other components may be introduced into a suitable mixer simultaneously or separately, and if necessary, mixed by stirring while melting by heating to obtain a homogeneous composition, thereby obtaining the mold underfill composition for TSVs according to the present invention. The mixer is not particularly limited, but a mortar machine equipped with a stirring device and a heating device, a Henschel mixer, a three-roll mill, a ball mill, a planetary mixer, a bead mill, etc. may be used. In addition, a suitable combination of these devices may be used.
[0128] The TSV mold underfill composition obtained in this way is thermosetting, and it is preferable to cure it in 0.1 to 3 hours under conditions of a temperature of 100 to 170°C, and more preferable to cure it in 0.25 to 2 hours.
[0129] The composition of the present invention can be used, for example, as an adhesive, sealant, or raw material for fixing, bonding, or protecting components constituting a semiconductor device or electronic components including various electronic components. The composition of the present invention is suitable as an underfill material for protecting electronic components or fixing them to a substrate, and in particular, as a mold underfill composition for TSV used in a technique in which sealing between a wafer and a chip and between each chip, and molding the external shape of an electronic component, are performed in a single process. As an example of an electronic component manufacturing process using such a technique, a compression molding process is illustrated in FIG. 1. A wafer (Fig. 1(A)) containing a plurality of stacked semiconductor chips is placed in a compression molding device equipped with a mold, and a mold underfill composition for TSV is applied to this wafer (Fig. 1(B)). This wafer is subjected to compression molding under heat, and subsequently, the mold underfill composition is cured by heating (Fig. 1(C)). Through this process, sealing between the wafer and the chip on which the semiconductor chip is mounted, and between each chip, as well as forming the external shape of the electronic component, can be achieved in a single process.
[0130] In addition, the present invention provides a cured product obtained by curing the mold underfill composition for TSV of the present invention. The present invention further provides an electronic component comprising the cured product of the present invention.
[0131] In the present invention, a semiconductor device sealed by the mold underfill composition for TSV of the present invention is also provided. In the present invention, a semiconductor package having a semiconductor device sealed by the mold underfill composition for TSV of the present invention is further provided.
[0132] (Example)
[0133] The present invention will be described below by way of examples, but the present invention is not limited thereto. In addition, in the following description, parts and % represent parts by mass and % by mass, respectively, unless otherwise noted.
[0134] Examples 1–6, Comparative Examples 1–5
[0135] A resin composition was prepared by mixing predetermined amounts of each component using a three-roll mill according to the formulation shown in Table 1. In Table 1, the amount of each component is expressed in parts by mass (unit: g).
[0136] (A) Epoxy resin
[0137] In the examples and comparative examples, (A) the compound used as the epoxy resin is as follows.
[0138] (A―1): Aminophenol-type epoxy resin (Product name: jER630, manufactured by Mitsubishi Chemical Corporation) (Epoxy resin having an aromatic ring)
[0139] (A-2): Aminophenol-type epoxy resin (Product name: jER630LSD, manufactured by Mitsubishi Chemical Corporation) (Epoxy resin having an aromatic ring)
[0140] (A-3): Aliphatic epoxy resin (Product name: YX7400, manufactured by Mitsubishi Chemical Corporation)
[0141] (B) Curing agent
[0142] In the examples and comparative examples, (B) the compound used as a curing agent is as follows.
[0143] (B-1): Liquid phenol novolak resin (Product name: MEH-8005, manufactured by Meiwa Kasei Co., Ltd.)
[0144] (B―2): 2,4―diamino―6―[2'―methylimidazolyl―(1')]ethyl―s―triazine (Trade name: Curzol 2MZ―A, manufactured by Shikoku Kasei Industry Co., Ltd.)
[0145] (C) Filler
[0146] In the examples and comparative examples, the compound used as (C) filler is as follows.
[0147] (C-1): Silica filler (Product name: SE2200SME, manufactured by Admatex Co., Ltd., average particle diameter: 0.6㎛, maximum particle diameter: 3㎛)
[0148] (C-2): Silica filler (Product name: SE1050SMO, manufactured by Admatex Co., Ltd., average particle diameter: 0.3㎛, maximum particle diameter: 1㎛)
[0149] (C-3): Silica filler (Product name: Admernano YA050C, manufactured by Admatex Co., Ltd., average particle diameter: 50 nm, surface treated)
[0150] (C―4): Silica filler (Product name: SE5200SME, manufactured by Admatex Co., Ltd., average particle diameter: 1.5㎛, maximum particle diameter: 10㎛)
[0151] (D) Carbon Black
[0152] In the examples and comparative examples, (D) the compound used as carbon black is as follows.
[0153] (D-1): Carbon Black (Product Name: Special Black 4, Manufactured by Orion Engineered Carbons Co., Ltd.)
[0154] In Table 1, “(D) Carbon Black Content” represents the amount (parts by mass) of (D) carbon black when the mass of (A) epoxy resin is 100 parts by mass.
[0155] (E) Silicon-based additives
[0156] In the examples and comparative examples, (E) the compound used as a silicon-based additive is as follows.
[0157] (E-1): Epoxy-modified silicone oil (Product name: SF8421, manufactured by Toray Dow Corning Silicones, Inc.)
[0158] (F) Coupling agent
[0159] In the examples and comparative examples, the compound used as (F) a coupling agent is as follows.
[0160] (F―1): 3―Glycidoxypropyltrimethoxysilane (Product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0161] (G) Migration inhibitor
[0162] In the examples and comparative examples, (G) the compound used as a migration inhibitor is as follows.
[0163] (G-1): Caffeine (manufactured by Fujifilm Wako Junyaku Co., Ltd.)
[0164] (I) Ion trap
[0165] In the examples and comparative examples, (I) the compound used as an ion trapping agent is as follows.
[0166] (I-1): Zr·Bi-based ion trap (Product name: IXE6136, manufactured by Dong-A Synthetic Co., Ltd.)
[0167] In the examples and comparative examples, the characteristics of the resin composition and the cured product were measured as follows.
[0168] (Viscosity of the composition)
[0169] The viscosity (unit: Pa·s) of each prepared resin composition was measured using a Brookfield HB type viscometer (using spindle SC4-14) under conditions of 25°C and 10 revolutions / minute. The results are shown in Table 1.
[0170] (Gel time of the composition)
[0171] Each prepared resin composition was dropped onto a stainless steel plate heated to 120±2℃ in a size of approximately 5 mmΦ, and a metal needle was attached to the resin composition at regular intervals to measure the time (unit: seconds) until the sagging disappeared using a stopwatch. In addition, in the mold underfill composition for TSV according to the present invention, the gel time is preferably 30 to 600 seconds, more preferably 60 to 570 seconds, and particularly preferably 90 to 540 seconds. If the gel time is within that range, injectability defects caused by gelation of the mold underfill composition for TSV can be suppressed, and the molding time during compression molding does not become excessively long, thereby improving productivity.
[0172] (Evaluation of Injectability of Mold Underfill Composition for TSV)
[0173] Silicon chips (length: 18 mm, width: 18 mm, thickness: 300 µm) were mounted on a silicon wafer (diameter 300 mm, thickness 760 µm) through nine spacers (disk-shaped, diameter 1 to 2 mm, thickness 20 µm). The spacers were placed at equal intervals along the diagonal of the silicon chips (see Fig. 2(B)). Four silicon chips were placed at equal intervals near the outer periphery of the silicon wafer using the above method (see Fig. 2(A)).
[0174] This silicon wafer, including both the silicon chip and the spacer, was placed in a compression molding device equipped with a mold (model number: WCM-300, manufactured by Apik Yamada Co., Ltd.). Subsequently, a mold underfill composition for TSV was filled into the mold, and compression molding was performed under conditions of a temperature of 120°C and a pressure of 250 kN. Afterward, the entire silicon wafer was coated by heating at this temperature for 400 seconds to cure the mold underfill composition for TSV, thereby forming a layer of the cured product of the mold underfill composition for TSV with a thickness of 500 μm (the silicon chip and spacer are sealed within it).
[0175] A seal was obtained by cutting a silicon wafer coated with a layer of cured material, removed from a compression molding device, at a position slightly away from the outer edge of the silicon chip. A test specimen for evaluating injectability was obtained by removing the silicon chip, cured material, and spacer from the seal by planar grinding until the thickness of the layer of cured material measured from the silicon wafer was approximately 10 μm.
[0176] The polished side of the obtained test specimen was observed visually or under a microscope (magnification: 100x). If no voids were found in the test specimen, or if the maximum width of the voids found in the test specimen was less than 100㎛, the injectability was evaluated as ○ (see Fig. 3(B)), and if the maximum width of the voids found in the test specimen was 100㎛ or more, the injectability was evaluated as × (see Fig. 3(A)).
[0177] (Production of hardened material)
[0178] A cured product was obtained by heating each prepared resin composition at 150°C for 1 hour using a dryer.
[0179] (Bias HAST test of cured material)
[0180] Figure 4 shows a schematic diagram of a comb-shaped electrode used to evaluate insulation reliability by a bias HAST test. This comb-shaped electrode consists of a polyimide film substrate (thickness 38 μm) and copper wiring patterned thereon (wiring width 15 μm, inter-wire pitch 30 μm, thickness 8 μm, tin plating (thickness 0.2 ± 0.05 μm)). A mold underfill composition for TSV was applied to this comb-shaped electrode to a thickness of 150 μm, and the mold underfill composition on the comb-shaped electrode was cured by heating at 150°C for 1 hour using a dryer to obtain a test specimen. This test specimen was mounted in a HAST device (model number: PC-422R8, manufactured by Hirayama Corporation), and the electrical resistance value was continuously monitored under conditions of 85% relative humidity and 130°C with a bias voltage of 3V applied. The time (unit: hr) from the start of the test until a short circuit occurred (when the electrical resistance value became 10 kΩ or less) was measured. The results are shown in Table 1. However, if no short circuit occurred within 168 hours, it is indicated as “Pass”.
[0181] (Chloride ions in hardened products (Cl - ) content)
[0182] A sample obtained by curing a prepared resin composition by heating it at 150°C for 60 minutes was ground to a size of approximately 5 mm. 25 cm³ of ion-exchanged water was added to 2.5 g of this sample, and the sample was placed in a PCT test tank (EHS-221M manufactured by Espec Co., Ltd., 121°C ± 2°C / 100% humidity / 2 atm) for 20 hours. The extract obtained by cooling to room temperature was used as the test solution. The chloride ion concentration of the test solution obtained in the above procedure was measured using an ion chromatograph (CLASS-VP manufactured by Shimadzu Corporation, using column IC-A3). The evaluation results of the chloride ion content are shown in Table 1.
[0183]
[0184] As is evident from Table 1, in any of Examples 1 to 6, in which (i) the content of (D) carbon black is 0.1 parts by mass or more and 1.5 parts by mass or less when (A) the mass of the epoxy resin is 100 parts by mass, and (ii) the content of chloride ions is 0.1 ppm or more and less than 11.0 ppm relative to the total mass of the mold underfill composition, no short circuit occurred within 168 hours from the start of the test in the bias HAST test conducted under the above conditions. Furthermore, in all of these examples, the mold underfill composition exhibited good injectability.
[0185] In this regard, in Comparative Examples 1 to 3, which do not satisfy either or both of the above requirements (i) and (ii), a short circuit occurred within 168 hours from the start of the bias HAST test.
[0186] In addition, in Comparative Example 4, where (C) filler did not contain filler with an average particle size of 0.1 μm to 1.0 μm, the injectability of the mold underfill composition was poor. In Comparative Example 5 as well, the injectability of the mold underfill composition was poor, but this is thought to be because (I) ion trapping agent contained many particles with a particle size larger than 1 μm. Furthermore, in Comparative Example 5, despite the excessive content of carbon black, no short circuit occurred within 168 hours in the bias HAST test. This is presumed to be because chloride ions were captured by (I) ion trapping agent.
[0187] Industrial applicability
[0188] The mold underfill composition for TSVs of the present invention exhibits good injectability and appropriate sealing properties. In addition, electronic components containing a cured product obtained by curing the mold underfill composition for TSVs of the present invention do not cause a short circuit over a long period of time during a bias HAST test. Therefore, by using the mold underfill composition for TSVs of the present invention, electronic components containing high-density wiring formed by techniques such as TSVs can be manufactured efficiently, and sufficient reliability can be imparted to such electronic components. Explanation of the symbols
[0189] 10: Silicon wafer 11: Silicon chip 12: Bump 13: Mold underfill composition for TSV 14: Mold 20: Silicon wafer (300 mm diameter) 21: Silicon Chip 22: Spacer (thickness 20㎛) 23: Cured product of mold underfill composition for TSV 30: Cured product of mold underfill composition for TSV 31: Spacer 32: Void
Claims
Claim 1 A mold underfill composition for TSV comprising the following (A) to (D): (A) epoxy resin; (B) curing agent; (C) filler; and (D) carbon black, and [In the formula, n is an integer from 1 to 15.] comprising an aliphatic epoxy resin represented by, wherein the (B) curing agent comprises an imidazole compound and a phenol compound, and the (C) filler comprises a filler with an average particle size of 0.1 μm to 1.0 μm, and when the total mass of the TSV mold underfill composition is 100 parts by mass, the content of the (A) epoxy resin is 10 to 35 parts by mass, and the content of the (C) filler is 65 to 90 parts by mass, and the content of the (B) curing agent is 1 to 20 mass% relative to the (A) epoxy resin, and when the mass of the (A) epoxy resin is 100 parts by mass, the content of the (D) carbon black is 0.1 parts by mass or more and 1.5 parts by mass or less, and also chloride ions (Cl ― A TSV mold underfill composition having a content of ) of 0.1 ppm or more and less than 11.0 ppm with respect to the total mass of the above TSV mold underfill composition. Claim 2 A mold underfill composition for TSV according to claim 1, wherein, when the total mass of (C) the filler is 100 parts by mass, the content of particles with a particle diameter greater than 1 μm in (C) the filler is less than 1.0 part by mass. Claim 3 A mold underfill composition for TSV according to claim 1 or 2, wherein (A) the epoxy resin further comprises an epoxy resin having an aromatic ring in its molecule. Claim 4 A mold underfill composition for TSV comprising (E) a silicon-based additive further comprising in claim 1 or 2. Claim 5 A mold underfill composition for TSV comprising (F) a coupling agent in accordance with claim 1 or 2. Claim 6 A mold underfill composition for TSV according to claim 1 or 2, further comprising (G) a migration inhibitor. Claim 7 A TSV mold underfill composition according to claim 1 or 2, wherein, when the total mass of the TSV mold underfill composition is 100 parts by mass, the content of particles with a diameter greater than 1 μm is less than 1.0 part by mass. Claim 8 A semiconductor package having a semiconductor device sealed by a mold underfill composition for TSVs described in claim 1 or 2. Claim 9 delete Claim 10 delete
Citation Information
Patent Citations
Method of manufacturing semiconductor device
JP2012004329A
Liquid resin composition for underfill, electronic component device, and method of manufacturing electronic component device
JP2019083225A
Underfill material, semiconductor package and method for producing semiconductor package
JP2021119239A
